Hubungan Pengetahuan Mengenai Kontrasepsi dengan Kepatuhan Penggunaan Kontrasepsi pada Wanita Usia Subur di Kecamatan Kasemen - I Made Arya Subadiyasa; Kania Pradiva Maharani; Luluk Hermawati (Pusat Riset dan Inovasi Nasional, 2026)
The prevalence of married women of childbearing age using contraception in Serang City is 53.34%, the third lowest in Banten Province. In 2023, Kasemen District was recorded as the area with the lowest number of new contraceptive acceptors in Serang City (58% of the target). One of the main challenges of the family planning program is the high unmet need due to non-compliance with contraceptive use, which can reduce the effectiveness of contraception and increase the risk of unwanted pregnancies and maternal and child mortality. This study was conducted to analyze the relationship between knowledge of contraception and compliance to contraceptive use among women of childbearing age in Kasemen District. The study used an analytical observational design with a cross-sectional approach, involving 36 respondents selected by stratified random sampling. Data were collected using a validated contraceptive knowledge questionnaire and the 2017 SDKI questionnaire in the contraception section, and analyzed using Fisher's Exact test. The results showed that 58.3% of respondents had good knowledge and 72.2% were compliant in using contraception. Fisher's Exact test showed no significant relationship between knowledge and compliance with contraceptive use with a p-value of 0.26 (>0.05). The conclusion in this study is that there is no relationship between contraceptive knowledge and compliance with contraceptive use in women of childbearing age in Kasemen District. Compliance with contraceptive use may be influenced by other factors, such as the role of family planning cadres and access to free family planning services.